prove that::::::

Asked by Chaitanya Patel | 18th Jul, 2010, 09:37: AM

Expert Answer:

1) To prove that  A-B-C=A-BAC Proof: Note that by definition A-B=AB' A-B-C=AB-C'=ABC''=AB'Cby Demorgan's law                                                                        =AB'ACby distributive law                                                                          =  A-BAC2. To prove that A-BC=A-BA-CProof: L.H.S= A-BC                         = ABC'                        = AB'C' by De Morgan's law                        =AB'C'R.H.S = A-BA-C            = AB'AC'            =AB'C'            = L.H.S">

Answered by  | 18th Jul, 2010, 06:41: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.